The Quality of Cryopreserved Semen of Local Chickens Treated with Ringer’s Lactate-Egg Yolk Extender Supplemented with Glycine and Glucose - Junaedi; Isnaini, N.; Natsir, M. H.; Susilawati, T. (Faculty of Animal Science, IPB University, 2024)
The aim of this study is to investigate the potential of glucose, glycine, and a combination of glucose and glycine supplemented into Ringer’s lactate extender on the quality of pre- and post-cryopreservation of semen of local chickens. Semen samples were collected from KUB roosters. The research procedures involved formulation of the extender, semen collection, assessment of fresh semen, dilution, packaging, cryopreservation, storage, and subsequent assessment of cryopreserved semen. Parameters assessed in fresh, pre-cryopreservation, and post-thawed semen using computer-assisted semen analysis (CASA), included motility (total motility, progressive, static, and slow motilities), kinematics, spermatozoa morphology, malondialdehyde (MDA) concentration, and scanning electron microscopy (SEM). There were four treatments: T1= control, T2= 50 mM glucose, T3= 60 mM glycine, and T4= a combination of 50 mM glucose and 60 mM glycine. Each treatment was repeated 10 times. The results showed that the addition of 60 mM glycine and the combination of 50 mM glucose and 60 mM glycine effectively preserved total motility, maintained progressive motility, and reduced damage to the bent tail during the equilibration process (prior to cryopreservation). In addition, total motility, progressive motility, DAP, DSL, DCL, VAP, VSL, VCL, STR, and LIN were significantly increased after thawing. This approach also minimized the formation of MDA. Furthermore, observations using SEM showed comparatively more intact acrosomes compared to the other treatments. In conclusion, the addition of 60 mM glycine and a combination of 60 mM glycine and 50 mM glucose to Ringer’s lactate-egg yolk extender proved to be effective in preserving the quality of domestic chicken spermatozoa during semen cryopreservation.